Implementasi Murottal untuk Mengurangi Tingkat Nyeri pada Pasien Pre-operasi Sectio Caesarea - Zamron, Muhammad; Susanto, Amin; Susanti, Indah (Yayasan Inspirasi El Burhani, 2025)
Introduction: Sectio caesarea (SC) is a major surgical procedure often accompanied by significant pain and anxiety in the pre-anesthetic phase. Pain that is not properly managed can interfere with recovery and overall patient comfort. Nonpharmacological interventions, such as murottal Al-Qur’an therapy, have been shown to provide both psychological and physiological relaxation effects that help reduce pain and anxiety. Objective: The purpose of this service was to determine the effectiveness of murottal therapy in reducing pain levels among pre-anesthesia SC patients at RSI Banjarnegara. Method: This public service was conducted through collaboration between lecturers and students of Universitas Harapan Bangsa and RSI Banjarnegara. Thirty postpartum SC patients aged 19–45 years participated and received a 10-minute murottal therapy intervention of Surah Ar-Rahman verses 1–15. Pain levels were assessed before and after the intervention using the Numeric Rating Scale (NRS). Data were analyzed descriptively to evaluate changes in pain perception. Result: The findings showed that before the intervention, 53.3% of participants experienced moderate pain and 46.7% experienced severe pain. After listening to murottal, 90.0% reported mild pain and 10.0% reported moderate pain, indicating a significant reduction in pain levels. The majority of participants also expressed feelings of calmness and comfort during the therapy session. Conclusion: Murottal therapy proved effective as a nonpharmacological intervention to reduce pain and promote psychological and spiritual comfort in SC patients during the pre-anesthetic phase. It is recommended that hospitals integrate murottal therapy into preoperative care to support holistic, patient-centered nursing practice.